THE DYNAMICS OF SLOW MANIFOLDS - Ferdinand Verhulst; Taoufik Bakri (Journal of the Indonesian Mathematical Society, 2007)
After reviewing a number of results from geometric singular perturbation theory, we discuss several approaches to obtain periodic solutions in a slow manifold.Regarding nonhyperbolic transitions we consider relaxation oscillations and canard-like solutions. The results are illustrated by prey-predator systems.DOI : http://dx.doi.org/10.22342/jims.13.1.76.73-90